2007
DOI: 10.1021/jo061934u
|View full text |Cite
|
Sign up to set email alerts
|

Medium Effect on the Rotational Barrier of Carbamates and Its Sulfur Congeners

Abstract: The solvent effect on rotation about the conjugated C-N bond has been studied for methyl N,N-dimethylcarbamate (1), S-methyl N,N-dimethylthiocarbamate (2), O-methyl N,N-dimethylthiocarbamate (3), and methyl N,N-dimethyldithiocarbamate (4). The present investigation included experimental determination of activation parameters (DeltaH, DeltaS, and DeltaG) combined with theoretical calculations via both quantum and classical approaches. Rotational barriers were measured through dynamic NMR experiments in solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 57 publications
5
42
0
Order By: Relevance
“…As for chemical shift assignments, kinetic data obtained in this work for Me 2 N-CSSEt (especially G # ) are in good agreement with those of Sandström for Me 2 N-CS-SMe (66.5 ± 2 kJmol −1 in CDCl 3 and 65.2 ± 1.7 kJmol −1 in o-dichlorobenzene [ODC]) 4 and of Pontes et al 10 (62.4 ± 0.8 kJmol −1 in C 6 D 6 and 66.6 ± 0.8 kJmol −1 in DMSO-d 6 ). As expected, the high rotation barriers obtained for dithiocarbamates 1-5 are consistent with hindered rotation involving disruption of the N-CS partial double bond.…”
Section: Rotational Barrierssupporting
confidence: 88%
See 1 more Smart Citation
“…As for chemical shift assignments, kinetic data obtained in this work for Me 2 N-CSSEt (especially G # ) are in good agreement with those of Sandström for Me 2 N-CS-SMe (66.5 ± 2 kJmol −1 in CDCl 3 and 65.2 ± 1.7 kJmol −1 in o-dichlorobenzene [ODC]) 4 and of Pontes et al 10 (62.4 ± 0.8 kJmol −1 in C 6 D 6 and 66.6 ± 0.8 kJmol −1 in DMSO-d 6 ). As expected, the high rotation barriers obtained for dithiocarbamates 1-5 are consistent with hindered rotation involving disruption of the N-CS partial double bond.…”
Section: Rotational Barrierssupporting
confidence: 88%
“…6 For example, N-methylation of aromatic secondary amides or ureas causes a dramatic loss of their biological activity due to conformational change of the structures. 7 Other functional groups such as dithiocarbamates are expected to display similar properties, but a few conformational studies have been devoted to them 4,[8][9][10] or to some of their metal complexes. 8,11 We were even surprised to find in the literature a confusion with the broadened doublet at 4.61 ppm in the 1 H NMR spectrum of PhCH 2 NHCSSEt, which was assigned to NH proton resonance instead of CH 2 N of the minor conformer.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies on the rotational barriers of carbamates reported two possible transition states TS 1 and TS 2 , where the lone pair on the pyramidalized nitrogen is anti or syn to the carbonyl oxygen (Scheme ) . For methyl N , N ‐dimethylcarbamate, representing a typical carbamate, all quantum chemical calculations involving basis sets beyond 3‐21G* agree with each other in terms of the relative stability of the two transition states, i.e., that TS 1 is lower in energy than TS 2 , whereas the barrier heights depend slightly on the details of the level of theory and basis set used.…”
Section: Introductionmentioning
confidence: 92%
“…By dynamic NMR (DNMR) experiments, the rotational barriers can be estimated by lineshape analysis or from the coalescence temperature T C , i.e., the temperature where the exchange is fast enough that both rotamers are indistinguishable by NMR. Such DNMR studies have been carried out for amides, thioamides, amidines, carbamates, and thiocarbamates . The influences of different substituents on the rotational barriers have been extensively studied for amides (e.g., DMF) and amino acid derivatives, while carbamates are much less explored.…”
Section: Introductionmentioning
confidence: 99%
“…When an N atom was attached to a double bond (as in >NAC@O), its lone pair electron can delocalize over the p system forming an approximately planar three-atom framework (Pontes, Basso, & dos Santos, 2007). Due to the barrier to internal rotation around the NAC(O) bond in amides, H, O, C, N and atoms attaching Fig.…”
Section: X-ray Diffraction Analysis (Xrd)mentioning
confidence: 99%